PENGARUH HAPPINESS AT WORKLIFE DAN QUALITY OF WORKLFE TERHADAP KINERJA KARYAWAN DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL MEDIASI PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS) - Dafin Ardiano; Vivin Maharani Ekowati (POLITEKNIK LP3I JAKARTA, 2025)
Happiness at Worklife and Quality of Work Life (QWL) are essential strategies to improve employee performance. The declining quality of service at Baznas Microfinance indicates that the implementation of Happiness at Worklife and QWL has not been optimal, necessitating further research to understand their impact on employee performance, particularly with Organizational Citizenship Behavior (OCB) as a mediating variable. This study aims to analyze the influence of Happiness at Worklife and QWL on employee performance, with OCB as a mediating variable. The study's background lies in the observed decline in service quality at Baznas Microfinance, reflecting suboptimal implementation of Happiness at Worklife and QWL, which has affected employee motivation and performance. The research employs a quantitative approach with an explanatory research design. The study population consists of 66 employees at Baznas Microfinance, with a sample of 50 respondents selected using the purposive sampling method. Data were collected through a Likert scale-based closed questionnaire and analyzed using IBM SPSS software. The results indicate that Happiness at Worklife and QWL significantly influence employee performance. OCB was found to partially mediate the relationship between QWL and employee performance, but the mediating effect of OCB on the relationship between Happiness at Worklife and performance was not significant.This study contributes theoretically by emphasizing the importance of QWL in enhancing performance through OCB, while Happiness at Worklife requires a tailored approach to foster a positive impact on performance. The practical implications of this research highlight the need for Baznas Microfinance management to enhance the quality of work life through policies that support work-life balance, fair compensation, and an OCB-based work culture. Additionally, strategies to improve work happiness should focus on aspects that effectively boost employee motivation and productivity.